The Role of Transaction Costs in Risk Management of Investment Projects - USMANOVA, Natalya V.; ORLOVA, Nina A.; ORLOVA, Nina A. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
This article is devoted to the role of transaction costs in the risk management of the investment project. Transaction costs are divided into groups that are in the course of investment project implementation. Then we describe the types of transaction costs included in each group. The structure and role of transaction costs considered by the example of investment construction projects. The proposed economic-mathematical model of risk management of investment project in the market with high transaction costs allows selecting an investment building project with the best characteristics in terms of acceptable level of risk. In the article, the influence of transaction costs on the risks of various phases of the investment project is analyzed and the model of transaction cost accounting is proposed when analyzing an investment project.
Keywords: investment project; phases of project; assessment of efficiency; transaction costs; risks